2019
DOI: 10.3390/jcm9010075
|View full text |Cite
|
Sign up to set email alerts
|

A Translational Study of TNF-Alpha Antagonists as an Adjunctive Therapy for Preventing Hemophilic Arthropathy

Abstract: Repeated intra-articular hemorrhages lead to hemophilic arthropathy in severe hemophilia. Inflammation and pro-inflammatory cytokines (e.g., tumor necrosis factor alpha (TNFα)) might be involved in this pathogenesis. We hypothesized that anti-TNFα may provide adjuvant protection for hemophilic arthropathy management. We measured TNFα in synovial lavage from hemophilia mice subjected to hemarthrosis induction and synovial fluid from patients with hemophilic arthropathy (n = 5). In hemophilia mice, recurrent hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
(70 reference statements)
0
3
0
1
Order By: Relevance
“…TNFα, on the other hand, remained unchanged in the plasma of mice with hemarthrosis and increased only insignificantly in hemophilia patients, which is in line with previous reports. 24 25 Previous data also reinforce a role of IL-6 in the natural history of hemophilic arthropathy as the IL-6/sIL-6Rα complex has been shown to trigger proliferation in synoviocytes and subsequent fibrotic remodeling of the synovia in hemophilia mice. 15 27 Taken together, these findings could be relevant for assessing the effect of bleeding on joint health in hemophilia patients as we found sIL-6Rα to be specifically upregulated in hemophilia patients with recent bleeding in conjunction with IL-6.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…TNFα, on the other hand, remained unchanged in the plasma of mice with hemarthrosis and increased only insignificantly in hemophilia patients, which is in line with previous reports. 24 25 Previous data also reinforce a role of IL-6 in the natural history of hemophilic arthropathy as the IL-6/sIL-6Rα complex has been shown to trigger proliferation in synoviocytes and subsequent fibrotic remodeling of the synovia in hemophilia mice. 15 27 Taken together, these findings could be relevant for assessing the effect of bleeding on joint health in hemophilia patients as we found sIL-6Rα to be specifically upregulated in hemophilia patients with recent bleeding in conjunction with IL-6.…”
Section: Discussionmentioning
confidence: 83%
“…22 23 The resulting secretion of IL-1β, IL-6, and TNFα has been strongly implicated in causing typical complications of joint bleeds such as synovitis, cartilage erosion, and bone loss. 15 24 25 26 The association between blood-induced inflammation and arthropathy was reiterated in our mouse model of hemarthrosis, where the fibrous remodeling of the punctured knee joint was preceded by a large increase of plasma IL-6. TNFα, on the other hand, remained unchanged in the plasma of mice with hemarthrosis and increased only insignificantly in hemophilia patients, which is in line with previous reports.…”
Section: Discussionmentioning
confidence: 91%
“…Zhang et al reported a significant TNF-α accumulation was found in the hemorrhagic tissues of the injured knee and strong TNF-α gene upregulation observed since day 3 up to 30 days after hemarthroses. Elevated TNFα level was found in the synovial fluid and plasma which 6 BioMed Research International TNF-α level in synovial fluids was 5.2-20 folds higher than in plasma (p < 0:05) in PWHA [28].…”
Section: Discussionmentioning
confidence: 91%
“…A história natural da hemofilia é marcada por sangramentos articulares espontâneos, cuja recorrência leva à artropatia hemofílica, um processo que combina sinovite, hiperplasia sinovial, destruição da cartilagem e do osso periarticular 36 Resultados preliminares sugerem que o bloqueio da via do TNFα por anticorpos monoclonais pode ser uma alternativa de controlar a sinovite e potencialmente frear a progressão da lesão articular 76,77 .…”
Section: Discussionunclassified